FUNDAMENTAL IMPACT ON SHARE PRICES: EVIDENCE FROM INDONESIA - Dwi Inggarwati Rahayu , Bustanul Ulum , Rusdiyanto ,Mochamad Syafii , Dini Ayu Pramitasari , Firdaus Indrajaya Tuharea (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to evaluate the fundamental impact on share price of banking sector companies listed on the Indonesian Stock Exchange. This paper uses a quantitative approach with the process of finding knowledge using data in the form of numbers as a generalizable tool to prove a hypothesis. Variable data to measure fundamentals as measured by Return on Assets, Return on Equity and Net Profit Margin are taken from the company's financial statements and the Indonesia Stock Exchange website at www.idx.co.id, www.ojk.go.id, www.bi.go.id and www.yahoofinance.com. The results of this study indicate that Return on Assets and Net Profit Margin have a positive and significant effect on share prices, so that these findings can be used by investors in conducting fundamental analysis that has relevant information. Meanwhile, Return on Equity has no effect on stock prices, meaning that the Return on Equity tends not to have value relevance to the price of banking shares listed on the Indonesia Stock Exchange. The research results are recommended for banking customers to increase the effectiveness and efficiency of banking performance and to contribute to the banking literature.